2004
DOI: 10.1161/01.cir.0000130644.78677.2c
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Differences in Acute Aortic Dissection

Abstract: Background-Few data exist on gender-related differences in clinical presentation, diagnostic findings, management, and outcomes in acute aortic dissection (AAD). Methods and Results-Accordingly, we evaluated 1078 patients enrolled in the International Registry of Acute Aortic Dissection (IRAD) to assess differences in clinical features, management, and in-hospital outcomes between men and women. Of the patients enrolled in IRAD (32.1%) with AAD, 346 were women. Although less frequently affected by AAD (32.1% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
324
8
14

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 456 publications
(369 citation statements)
references
References 39 publications
23
324
8
14
Order By: Relevance
“…Earlier studies have identified long‐term predictors of morbidity and mortality in AAD, including old age,13, 14 female sex,15 a history of atherosclerosis,4 and impaired renal function,16 all of which may be more representative of a patient's high‐risk clinical background than the severity and nature of the AAD itself. Indeed, as of yet, there may be no effective and simple marker available for evaluating severity of AAD, predicting long‐term clinical outcomes, and optimizing surgical management.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have identified long‐term predictors of morbidity and mortality in AAD, including old age,13, 14 female sex,15 a history of atherosclerosis,4 and impaired renal function,16 all of which may be more representative of a patient's high‐risk clinical background than the severity and nature of the AAD itself. Indeed, as of yet, there may be no effective and simple marker available for evaluating severity of AAD, predicting long‐term clinical outcomes, and optimizing surgical management.…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, the mortality rate was low for patients with AAD, as only one death occurred during the study period. Prior authors have reported the mortality rate for AAD, whether with or without MFS, to range from 18-38 % in pediatric and adult groups [4,5,10,15]. Using the PHIS database, Shamszad et al [11] reported that AAD was rare in pediatric patients with connective tissue diseases, including MFS, Ehlers-Danlos syndrome, and others, and mortality was 22.2 %.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Stanford classification, acute type A dissection was defined as any dissection that involved the ascending aorta and/or aortic arch and acute type B as that involving the descending aorta (without any tear in or involvement of the ascending aorta) presenting within 14 days of symptom onset [6,7]. ELs were defined as leakage of CM outside the graft, but within the aneurysm sac and were classified into five types depending upon the origin of the leak (Table 1) [8e10].…”
Section: Cta Protocol and Imagine Analysismentioning
confidence: 99%